Synthesis and Characteristics of Al(III)-Imprinted Silica Gel Sorbent - Ding, Lan-Lan; Zhong, Zhi-Jing; Long, Su-Qun; Deng, Yi; Hui, Yong-Qing; Lin, Tao; He, Xiao-Bo; Zhou, Yin-Hang (Asian Journal of Chemistry, 2013)
In this study, a new Al(III)-imprinted silica gel sorbent was synthesized by a surface imprinting techniquefor selective extraction or preconcentration of Al(III). Compared with non-imprinted polymer particles, the aluminium ion-imprinted silica gel (Al-IIISG) had higher selectivity and adsorption capacity for Al(III). The maximum static adsorption capacity of the aluminium ion-imprinted silica gel for Al(III) was 12.79 mg/g. Results suggested that aluminium ion-imprinted silica gel was a material of efficient, low-cost for Al(III) separation and concentration.